High resolution reconstruction of modern charcoal production kilns: An integrated approach combining dendrochronology, micromorphology and anthracology in the French Pyrenees. (20th August 2021) - Fouédjeu, Léonel; Saulnier, Mélanie; Lejay, Mathieu; Dušátko, Martin; Labbas, Vincent; Jump, Alistair S.; Burri, Sylvain; Buscaino, Sandrine; Py-Saragaglia, Vanessa
Abstract: Numerous charcoal kiln remains can still be found throughout the world, evidencing wood harvesting related to former industries. These remains represent effective sources and tools for studying (i) pre-industrial pressures on forest resources and (ii) past strategies related to woodland management. However, radiocarbon dating (AMS), which is the main tool to reconstruct the chronology of past charcoal manufacturing activity, doesn't provide sufficiently accurate dating, especially for the post-1650 period, due to the broad probability range of the dates resulting from wiggles in the calibration curve. In order to overcome the radiocarbon dating limitation and therefore refine the chronology of modern charcoal manufacturing, this paper proposes to apply an integrated approach combining archaeology, micromorphology, anthracology and dendrochronology. To characterise the archaeological record of a target charcoal kiln terrace from the "Forêt de Bernadouze", located in a historical iron production valley of the Northern Pyrenees, we combined classical stratigraphic analysis with a micromorphological study. The results highlight the multiperiod nature of the terrace, i.e. a palimpsest of multiple charcoal production episodes, revealing two major phases marked by an abandonment period between them. Subsequently, we constructed a beech charcoal-ring (n = 49) chronology cross-dated with the new "Forêt de Bernadouze" reference chronology from freshly felled, living beech trees (n = 24) to obtain the annual resolution of charcoal ring formation. Based on the new reconstructed master chronology covering the 1879–2016 period, we were able to calibrate the charcoal-ring chronology for the 1881–1941 period. Consequently, we (i) dated the charcoal production activity performed on the target terrace during the 1924–1942 period and (ii) identified a shift in the rate of use of the terrace, from one-off to high-intensive use. This study also provides new insights regarding (i) the particular nature of the archaeological record and (ii) the operating and timing of past charcoal-making practices in connection with silvicultural treatments.